2017
DOI: 10.1097/gox.0000000000001493
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Free Flap Breast Reconstruction Outcomes: Do Abdominal Scars Affect Bilateral Flaps?

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Unukovych et al found generally similar risk profiles but increased hematoma incidence at the recipient site in a cohort of women with prior c-sections who underwent abdominally based breast reconstruction compared with women without histories of c-sections. 29 However, despite our study's similar cohort size, demographics, and incidence of prior abdominal surgery, we did not find any significant associations between prior abdominal surgery and perioperative outcomes.…”
Section: Discussioncontrasting
confidence: 67%
“…Unukovych et al found generally similar risk profiles but increased hematoma incidence at the recipient site in a cohort of women with prior c-sections who underwent abdominally based breast reconstruction compared with women without histories of c-sections. 29 However, despite our study's similar cohort size, demographics, and incidence of prior abdominal surgery, we did not find any significant associations between prior abdominal surgery and perioperative outcomes.…”
Section: Discussioncontrasting
confidence: 67%